Open syllable lengthening and diphthongisation in Upper Middle High German: evidence from verse - Booth, J (Springer, 2023)
Despite a long history of scholarly interest, the relative chronologies (and even origins) of open syllable lengthening (OSL) and the diphthongisation of the Middle High German (MHG) high vowels /iː,yː,uː/ remain unclear. This paper, drawing on orthographic evidence from a thirteenth-century 'Parzival' MS, St. Gallen, Stiftsbibliothek, Cod. 857, provides new insights into these two key changes. The changes either maintained or increased the quantity of stressed vowels, leading to a net increase in the quantity of stressed syllables in MHG. Diphthongisation simply altered the segmental quality of already long monophthongs; only OSL increased the quantity of the vowels it affected. This paper argues that OSL was not a feature of the South Bavarian dialect of Cod. 857’s Hand III, although his dialect had certainly undergone diphthongisation. It is difficult to reconcile this picture with claims by Penzl, Kranzmayer and Wiesinger that OSL was present throughout the Bavarian dialect area by 1200. This paper challenges claims that diphthongisation was triggered by OSL via a phonological push-chain, maintaining that the two changes were independent. It is furthermore suggested that the scribe is uninterested in marking vocalic quantity, which—in the absence of OSL—was still consistent across inflexional paradigms. Instead, he uses the circumflex ‘length marker’ to indicate diphthongal quality. The scribes’ dialect thus represents a key turning point: diphthongisation was well progressed, but OSL had yet to occur.